Direct medical cost of adult Covid-19 ınpatients and ıts determinants at a university hospital - Medine Gözde Üstündağ; Nazım Ercüment Beyhun; Murat Topbas; Sevil Turhan (PLoS ONE, 2025)
Background and objectives The aim of this study is to determine the direct medical costs of adult cases diagnosed with Covid-19 and hospitalized at Karadeniz Technical University Faculty of Medicine Farabi Hospital (KTUFMFH). Methods This is a cost of illness study. The direct medical costs of adult cases who were hospitalized and treated for Covid-19 at KTUFMFH between 13.03.2020-12.03.2021 were examined. The study was retrospectively, on hospital perspective, using a prevalence-based approach and a bottom-up costing method. Per case costs, distribution of costs, and factors were examined for 113 cases. The determinants of the costs were evaluated via logistic regression analysis. Results The median cost per case was 263.55 (min: 28.30 – max: 18,947.60) USD [229.55 (min: 23.90 – max: 15,633.67) EUR]. One-day increase in hospitalization (O.R. = 2.600 and %95 C.I. = 1.576-4.289), the presence of chronic disease (O.R. = 15.130 and %95 C.I. = 1.644-139.216) and receiving oxygen inhalation therapy (O.R. = 15.238 and %95 C.I. = 1.784-130.157) have been identified to increase medical cost of Covid-19 inpatients. Conclusion Covid-19 hospital costs are of significant economic burden. The actions in order to lower the severity of the disease may play role to lower the medical costs in future coronavirus related pandemics.